Pengаruh Presepsi Mаnfааt, Kepercаyааn terhаdаp Minаt Penggunааn Mobile Bаnking BRI Dikаlаngаn Mаhаsiswа - Saiful Amrin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out: (1) Perceptions of Benefits of Interest in Using BRI Mobile Banking Among Students of the Economic Education Study Program for the 2022/2023 Academic Year (2) Trust Interest in the Use of BRI Mobile Banking Among Students of the Economics Education Study Program for the 2022/2023 Academic Year.The type of research used in this research is quantitative with a quantitative descriptive approach. The data collection technique used in this study is; (1) questionnaire, (2) observation and (3) documentation. The data analysis technique used is to use statistical data analysis with multiple linear regression formulas.The results of this study indicate that (1) there is a significant influence between the Variables of Perceived Benefits (X1) on interest in using Mobile Banking BRI among students wa Economics Education Study Program for the 2022/2023 Academic Year. With the results of the analysis showing that the value of tcount > ttable is 4.482 > 2.17881 and a significant value of 0.001 < α (0.05). (2) there is a significant effect between v Trust Variable (X2) on Interest in Using Mobile Banking for Students of Economic Education Study Program Year Academic2022/2023 . The results of the analysis show that the tcount > ttable is 2.253 > 2.17881 and a significant value is 0.044 <α (0.05).Therefore, it is recommended to the parties as follows: (1) For BRI Bank to optimize and improve the server in mobile banking services against out-of-pocket users. (2) When the researcher is continued, the researchers will not be used for the use of the mobiles and the mobile will be the user of mobile bare, in the future, the to participate in conducting research.Students of the Flores University economics education study program who use Mobile Banking services must remain careful when making transactions, because not everyone is the bank's responsibility. (4) For economic education study programs, it is hoped that the results of this research will provide references and experience for educators in using Mobile Banking.